GAMBARAN PENGETAHUAN IBU-IBU DESA PANGGUNGHARJO MENGENAI KANKER PAYUDARA DENGAN PERILAKU SADARI - Solikhah, Solikhah; Tukiyo, Intan Wahyuni; Al Ayubi, Muhammad Kamaludin; Rukmana, Dewi; Hartuti, Eka Putri; Rahmawati, Kiki; Santoso, Budi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
ABSTRACT Breast cancer is one of the PTM which is still a big problem in Indonesia with a fairly high number of deaths in women. To reduce mortality and the incidence of breast cancer can be done by screening early breast cancer, one of them by doing breast self-examination or breast self-examination. This research aims to find out the level of knowledge of Panggungharjo Village mothers about breast cancer with BSE behavior. This research was conducted with a quantitative descriptive approach. The sample of this research was taken using accidental sampling technique in the mothers of Panggungharjo Village, Bantul Regency, Yogyakarta. With a total sample of 35 people and using a questionnaire as a research instrument. The results showed that the knowledge of the mothers of Panggungharjo Village had increased from 65.71% to 68.57% and was classified in the good category. So that the knowledge to do and apply BSE behavior in everyday life will be better.